Prevalence and Incidence of Intentional and Unintentional Poisoning in a Tertiary Care Hospital, Erode, India - Narayanan, Lokesh; Kaliyaperumal, Kamesh; Ramalingam, Kameswaran; Balasubramanian, Rajkapoor (Journal of Health and Allied Sciences NU, 2024)
Poisoning is a significant burden in developing countries, with high fatality rates due to deliberate self-harm and unintentional exposures. This study aimed to raise awareness and provide guidance on poison consumption in a tertiary care hospital in Erode. A cross-sectional study over 6 months involved 377 poisoning cases. Females aged 21 to 30 years, semi-urban residents, and illiterate individuals were found to be the vulnerable groups. Rat killers and tablets were common poisoning agents, often linked to family problems. Comprehensive approaches, addressing mental health, family support, and health care access, are needed. Raising awareness, counseling, and educating high-risk individuals are essential preventive measures. Interventions enhanced poisoning management knowledge and coping strategies, emphasizing the importance of integrated efforts to combat poisoning's socioeconomic impact.
Keywords: Prevalence; cross-sectional study; poison; interventions; intentional; unintentional